0377 The Impact of Abuse during Childhood on Adult Sleep and the Moderating Influence of Bedroom Safety. (27th April 2018) - Ellis, J G; Bastien, C H; Gallagher, R; Alfonso-Miller, P; Hale, L; Branas, C; Perlis, M L; Grandner, M A
Abstract: Introduction: Exposure to child abuse may lead to long-term adverse changes in hyperarousal, health, and stress regulation that may predispose the survivor to insomnia and other sleep disturbances in adulthood. This may be especially true when the bedroom is viewed as unsafe. The aim of the present study was to examine whether exposure to child abuse was associated with poor sleep in adulthood and how this was moderated by perceived bedroom safety. Methods: A diverse sample of 1, 002 community-based adults age 22–60 participated in the Sleep and Healthy Activity, Diet, Environment, and Socialization (SHADES) study. Participants completed measures of sleep - insomnia symptoms (ISI), sleep quality (PSQI) and typical sleep duration, their levels of current perceived bedroom safety (response categories yes or no) and indicated whether they had a history of childhood abuse (defined as either physical or sexual abuse - yes or no). Covariates included age, sex, race/ethnicity, education, and body mass index. Mediating influence of depression and anxiety were also examined. Results: Of those who completed the survey, 204 (20.36%) indicated a history of childhood abuse and this was associated with poorer sleep in terms of insomnia symptoms, sleep quality and sleep duration. A safety-by-abuse interaction was significant for insomnia, sleep quality, and sleep duration. In stratified analyses, those who suffered abuse but perceived their sleep environment as safe reported worse insomnia (B=2.39, p<0.0001) and sleep quality (B=1.47, p<0.0001) and shorter sleep duration (B=-0.40, p=0.006) relative to those with no history of abuse. In those whose sleep environment was perceived as unsafe, the impact of abuse was 20% greater for insomnia, 52% greater for sleep quality and 38% reduced for sleep duration. When depression/anxiety were included in models, relationships were generally maintained. Conclusion: The findings suggest that abuse history may impact presentation of insomnia, and appears to be amplified by perceiving the bedroom as an unsafe environment. Both history of abuse and perceived bedroom safety should be routinely asked and accounted for by sleep clinicians. Support (If Any):